The conservation worthiness of the environment of the Black and Liesbeeck River confluence area - Tilanus, Edward Frank (Department of Environmental and Geographical Science, 2022)
This dissertation aims to interpret the environmental factors which will inform land use planning for the Liesbeek-Black River Confluence Area. It is in partial fulfilment of the academic requirements for a Master of Philosophy (M.Phil) in Environmental Science through the Department of Environmental and Geographical Science (ENGEO) at the University of Cape Town (UCT). This document follows on from the Baseline Information Document (BID) produced by the 1994 Masters students and should be read in combination with that document. This dissertation uses the information provided in that document, and with the support of other materials and insights, draws conclusions for the most appropriate land use for the study area. A Statement of the Problem, the Aim, Approach and Philosophy adopted towards the Study Area in this Dissertation. The problem is perceived to be the substantial public objection to recent proposed developments in the study area. These objections have revolved around the method of disposal of State land, the fragmentation of public open space and the apparent disregard of the authorities for the natural historical legacy of the Cape Peninsula. The aim of the study is to demonstrate that the study area holds potential as a public amenity. This could be self-supporting and of benefit to future generations in the region and is therefore worthy of conservation. The approach adopted in this dissertation is that the study area is unsuitable for any use other than as a conservation and recreational reserve. This could prove its value in a substantially more populated and informed future Cape Town. Urban open space, which constitutes wildlife habitat, is required locally to meet increased human population habitation needs. This need is perceived to be global phenomenon. There is concern that the accumulated consequence of these local demands, will result in a profound negative effect on the Biosphere.